Evaluating longitudinal aspects of cerebrospinal fluid biomarkers for cognitive disease - Basic, Emir (My University, 2022)
The most common neurodegenerative disease that millions are affect by today are Alzheimer’s disease (AD) and Parkinson’s. Diseases and disease progression can be diagnosed and evaluated using cerebrospinal biomarkers. The aim of this project is to evaluate these biomarkers (Aβ 1-42, T-tau, P-tau, albumin ratio, soluble APPα/β) to certain variables and how they affect cognition. Patient data was obtained from the participants of in the Gothenburg Mild Cognitve Impairment Study, and contained baseline data and date from a check up 2 years after baseline. The group included 862 patients and controls. Statistical analysis was performed to calculate normality plots, distribution between groups, medians, interquartile ranges Bonferroni correction and linear regression analysis. Results showed that there were significant differences in baseline for the variables between the groups. For year 2, there were significant differences between all the group for the variables expect for sAPPα. The delta values showed significant differences between the groups in biomarkers P-tau and sAPPβ and all the cognition test. Linear regression analysis showed that all biomarkers went toward the state that is considered sick with increasing age, but biomarkers sAPPα/β were considered stable. Results showed that some biomarkers are better for diagnosing certain diseases and the new biomarkers could potentially introduce a more accurate way of predicting cognitive disease.